2022
DOI: 10.1590/0034-737x202269050012
|View full text |Cite
|
Sign up to set email alerts
|

Least limiting water range in Oxisol under two conservation tillage systems in sugarcane farming

Abstract: The Least Limiting Water Range (LLWR) is an indicator of soil physical quality, contributing in information to propose soil management systems in agricultural farming process. This work aimed to assess the usage of LLWR and critical soil bulk density for physical-water quality evaluations, as well as its effect on sugarcane farming under notillage and reduced-tillage, in Oxisol. Undisturbed soil samples were collected in 0.00-0.10 and 0.10-0.20 m soil layers, to determine the following attributes: soil bulk de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Some of them were lower than this value; therefore, they are in a state considered non-restrictive to the development of the plants, showing satisfactory aeration conditions. It should be observed that, according to SILVA et al ( 2020), aeration porosities smaller than 0.10 m 3 m -3 did not cause a significant reduction in gas exchange values and corn growth and that values greater than 0.10 m 3 m -3 are more limiting for plants due to changes in soil attributes such as resistance to penetration and least limiting water range (SOUZA et al 2022).…”
Section: Soil Attribute Analysismentioning
confidence: 94%
“…Some of them were lower than this value; therefore, they are in a state considered non-restrictive to the development of the plants, showing satisfactory aeration conditions. It should be observed that, according to SILVA et al ( 2020), aeration porosities smaller than 0.10 m 3 m -3 did not cause a significant reduction in gas exchange values and corn growth and that values greater than 0.10 m 3 m -3 are more limiting for plants due to changes in soil attributes such as resistance to penetration and least limiting water range (SOUZA et al 2022).…”
Section: Soil Attribute Analysismentioning
confidence: 94%
“…Sá et al [24], evaluating soil compaction in sugarcane, stated 3.8 MPa of SPR limits plant root growth. However, Souza et al [15] found that critical root development is above 2 MPa.…”
Section: Soil Resistance Penetration In Rowsmentioning
confidence: 97%
“…Luz et al [7] found similar results, indicating traditional soil management does not benefit to alleviate compaction when compared to a conservationist system. According to Souza et al [15], soil preparation is a high-cost operation in sugarcane renovation fields, and results from soil preparation are not maintained during the crop cycle; this occurs due to heavy machine traffic and rearrangement of soil particles in wheel interaction (Marques Filho et al) [16] and weathering agents such as rain and wind [18].…”
Section: Soil Resistance Penetration In Rowsmentioning
confidence: 99%
See 2 more Smart Citations